Rethinking Customer Experience in Post-Pandemic Era A Case Study of J and T Express - Binti Jais, Nur A’rifah; Binti Mohd Dahari, Noor Naidatul Natasya; Binti Ahmad Fikri, Nur Adila; Binti Remli, Normashitah; Setya Putra, Hendrawan Purnama (International Journal of Tourism and Hospitality in Asia Pasific, 2023)
In logistics management, customer satisfaction is the crucial factor in providing service quality. J&T Express has proven to be successful and very influential in providing its customer services. While constant innovation is essential to providing better services to consumers. The purpose of this research is to identify the distinguished services offered and ways that customers derived their satisfaction during this pandemic. The covid-19 pandemic has brought massive changes in the way J&T Express offered its services as we can see that today's society makes extensive use of internet transactions and courier services. This is due to the existing state of affairs, which is plagued by pandemics. As a result, numerous services will play a part in ensuring that clients receive high-quality services post-pandemic. This research paper will focus on identifying the factors that influence customer satisfaction in using J&T delivery service. A structured questionnaire & survey will be conducted to gather customers’ responses in Malaysia and Indonesia. The study will highlight aspects to provide a different perspective and greater customer satisfaction during and post-pandemic covid-19. The survey data will help to analyse and suggest new ways of creating customer experiences.